Performance evaluation indicator system for the operation and management of Olympic venues - Wang, Z.; Zhan, W. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: In the of absence of a performance evaluation indicator system for the operation and management of Olympic venues, this study focused on establishing such a system. Methods An on-site inspection of the Weightlifting Gym of the 2008 Beijing Olympic Games was conducted. Administrators were interviewed and surveyed to identify the important performance evaluation indicators during operation and management. A new indicator system for performance evaluation of the gym was developed based on the balanced scorecard. This indicator system was more balanced and comprehensive . Moreover, the AHP method was employed to determine the weighting of indicators.